The synergistic effect of inflammation and metabolic syndrome on intraocular pressure: A cross-sectional study - Lee, I-Te; Wang, Jun-Sing; Fu, Chia-Po; Chang, Chia-Jen; Lee, Wen-Jane; Lin, Shih-Yi; Sheu, Wayne Huey-Herng (Medicine (Baltimore), 2017)
Intraocular pressure is associated with metabolic syndrome. C-reactive protein (CRP) is associated with cardiovascular disease, irrespective of the presence of metabolic syndrome. In this study, we examined the synergistic effect of CRP and metabolic syndrome on intraocular pressure.A total of 1041 subjects were included for data analyses in this cross-sectional study. Intraocular pressure was measured using a noncontact tonometer, and serum CRP levels were measured using a commercially available kit.The intraocular pressure was significantly higher in the subjects with metabolic syndrome than in those without (14.1 ± 3.0 vs 13.4 ± 3.0 mm Hg, P = .002). Furthermore, intraocular pressures significantly increased according to CRP tertiles (13.1 ± 3.0, 13.7 ± 3.0, and 13.8 ± 3.0 mm Hg from the lowest to highest tertile of CRP, respectively; P = .002). The highest intraocular pressure was observed in subjects with metabolic syndrome in the highest CRP tertile (P value for trend < .001). Multivariate linear regression analysis revealed that the influence of CRP was independent of metabolic syndrome and that high CRP levels were significantly associated with high intraocular pressure (95% confidence interval: 0.080-1.297, P = .027).In conclusion, systemic inflammation, reflected by serum CRP levels, is associated with high intraocular pressure in subjects with and without metabolic syndrome.